Guarantee on all the Assets of the Debtor in Insolvency - Bularca Anca Roxana (Perspectives of Business Law Journal in tha Third Millenium, 2013)
Unsecured creditors in the insolvency of the debtor's creditors are those who do not have collateral security against the debtor's assets and who are not accompanied by liens privileges whose claims are current at the opening proceedings and claims us for current activities during observation. In the matter of the bankruptcy secured creditors set for secured debts are claims receiving collateral on the debtor's property, whether it is the primary obligor or third party guarantee to persons benefiting from collateral. The secured creditor's secured claim in the insolvency procedure is given by the value of collateral assessment arising after the opening of insolvency proceedings the debtor. These special legal provisions contained in the bankruptcy, derogating from the common law, they often generate different practical situations and have created jurisprudence. In judicial practice of insolvency have encountered situations where the creditor security budget, which requires to be entered in the final table of the debtor in the category of secured creditors, the debt claim, warranty claims for his claim is the universality of the debtor's assets. The study on which we focused includes analysis of these categories of claims in insolvency proceedings and the solutions adopted in judicial practice.